Evolutionism and dialectics in the origin of humankind - García-Vega Redondo, Laura (2025)
According to evolutionism, the difference between the human species and the animal species is only gradual and quantitative, depending on the amount of reflexes capable of learning each species. For dialectical materialism the difference is qualitative; Each of these two species has a different brain with different functions.